The Berenstain bears and the trouble with friends - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1986)
Lonely without friends her age to play with, Sister Bear is delighted when a new little girl cub moves into the house down the road.